Reinvestigation of Fast Radio Burst Host Galaxy and Event Rate Density - W. Q. Ma; Z. F. Gao; B. P. Li; C. H. Niu; J. M. Yao; F. Y. Wang (The Astrophysical Journal, 2025)
Fast radio bursts (FRBs) are radio signals that last milliseconds. They originate from cosmological distances and have relatively high dispersion measures (DMs), making them excellent distance indicators. However, the origins of the FRB remain to be resolved. With its wide field of view and excellent sensitivity, CHIME/FRB has discovered more than half of all known FRBs. As more and more FRBs are located within or connected with their host galaxies, the study of FRB progenitors is becoming more important. In this work, we collect the currently available information related to the host galaxies of FRBs, and the Markov Chain Monte Carlo analysis about limited localized samples reveals no significant difference in the median of DM _host between repeaters and nonrepeaters. After examining and selecting CHIME/FRB samples, we estimate the local volumetric rate density of repeaters and nonrepeaters, accounting for different DM _host contributions, and compare with rates of predicted origin models and transient events. Our results indicate that DM _host significantly affects volumetric rates and offer insights into the origin mechanisms of FRB populations.